House of Tranquility / Nur Afifah M Azman... [et al.] - Marandan, Kasmia; Adanan, Salwana; Masinin, Nurul Izzah; Amat Javavi, Nur Farina; M Azman, Nur Afifah (2013)
Service type of business is said to be quite tough to run as it needs a complicated planning. It also refers to intangible goods where people can not touch the good yet still can be consumed. The idea of having service type of business is because we know it's a challenging task but we can feel that the opportunity is big. We have the feeling that we might have the chance to be a successful pioneer company which can provide a business type of product which is in the form of hospitality and care. Serving the old folks may not be a favorable activity that many people want to venture in. That's why we use this opportunity to make a house for the elders to be sent to. In Malaysia, especially in Peninsular Malaysia, there's quite a lot of old folk's nursery have been created. Unfortunately, the amount of this type of service being provided is almost zero in Sabah. The elderly care center does exist in Sabah, but they're not doing it for the purpose of business, instead, they just want to help out the elderly without getting any payment. That is why we come up with the idea of establishing the HOUSE OF TRANQUILITY. This so called house is created for the elderly to enjoy their relaxing time in our premise which is located on top of a hill which is also not far from the Kota Kinabalu city.The planning for this business requires a lot of works and researches that we need to accomplish as the elders are not the same as children. They know what they really want and desire in order for them to feel comfort.